Gender Disparity and Housing Development: Examining Socioeconomic Barriers and Policy Solutions in Nigeria - Makinde, Olusola Oladapo; Makinde , Olubukunmi Temitope (Journal of Contemporary Urban Affairs, 2025)
Gender disparity (GD) significantly impacts housing development, especially in developing countries like Nigeria, where socioeconomic and cultural barriers constrain equitable housing access. This study investigates the features and effects of GD on housing development in Iwo Central Local Government Area, Osun State, Nigeria. Using a mixed-method approach, data were collected from 328 respondents through questionnaires and analyzed using descriptive and inferential statistics, including indices and ANOVA. Key findings highlight societal mindsets as the most influential feature of GD, followed by lack of bodily autonomy and employment equality, with respective relative significance indices (RSIs) of 4.23, 4.06, and 4.00. Denied access to housing and homelessness emerged as the most critical effects of GD, with effects indices (EGDIs) of 4.36 and 4.31. Regression analysis revealed a significant relationship between GD characteristics and housing development (F = 99.964, p = 0.04), emphasizing the pervasive impact of GD on housing equity. The study concludes that GD restricts women's access to adequate housing, perpetuating socioeconomic inequalities. Recommendations include promoting gender-responsive housing policies, enhancing women's access to affordable housing finance, and integrating gender equity into urban planning and housing design. Addressing GD is crucial for fostering inclusive, equitable, and sustainable housing development in Nigeria.